Analisis Kandungan Zat besi (Fe) Pada Daun Kelor (Moringa oleifera Lam.) Yang Tumbuh dengan Ketinggian Berbeda di Daerah Kota Baubau - Hamzah, Hasty; Yusuf, Nur Rahmah (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2019)
Moringa oleifera Lam. is ones of the multipurpose plants. All parts of the plants are useful to human life and efficacious as a medicine. Moringa oleifera Lam can grow in the lowlands and highlands to an altitude of 1000 masl. This study was conducted to determine the levels of iron (Fe) in Moringa oleifera Lam leaves that grew at different heights using Atomic Absorption Spectroscopy (AAS) the results shows the amount of iron (Fe) in the lowlands of 14 masl (Wameo Village) is 6.28 mg per 100 g of Moringa leaf, medium plains 58 masl (Kantalai Village) is 5.57 mg per 100 g of sample while in the highlands 318 masl (Kaisabu Subdistrict) is 3.86 mg per 100 g of sample. Factors that influence the amount of iron content in Moringa oleifera Lam leaves are height which further affects the intensity of sunlight, humidity. Other factors can be caused by soil conditions (texture, moisture, nutrient, and pH).